The Effect of Price, Land Area and Production Costs on Rice Farmer’s Income: Case in Bone Bolango Regency - Karsum Usman; Usman Moonti; Sri Endang Saleh (Jambura Equilibrium Journal, 2022)
This study aims to determine the effect of price, land area and production costs on the income of rice farmers in North Toto Village, Tilongkabila District, Bone Bolango Regency. Data collection techniques used in this study were observation, interviews, questionnaires, and documentation. With a total sample of 44 farmers in North Toto Village. This research method uses a quantitative approach with multiple linear regression model analysis. The results showed that the price had a negative and insignificant effect on the income of rice farmers in North Toto Village. This means that every 1% increase in price can reduce income by 0.237. Land area has a positive and significant effect on the income of rice farmers in North Toto Village. This means that every 1% increase in land area can increase income by 0.682. Production costs have a negative and significant effect on the income of rice farmers in North Toto Village. This means that every 1% increase can reduce income by -0.254. The coefficient of determination (R Square) is 0.596, this shows that the percentage of rice farmers' income variation which is explained by the variation of the independent variables, namely price, land area and production costs is 59.6% for the remaining 40.4% influenced by other variables.